MOTIVASI BERPRESTASI BIDANG USAHA TATA BUSANA SISWA KELAS XI DI SMKN 3 PEKANBARU - Siti Azura; Jaspar Jas; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this study is to know about Achievement Motivation on Feild of Buisness of Fashion Department of the students from class XI at SMKN 3 Pekanbaru. This is a descriptive study, with a quantitative approach. The population of this study is the students from class XI of Fashion Department at SMKN 3 Pekanbaru. The sample of this study is 34 studenst from population were taken with random sampling technique. Instrument of this study is using a questionnaire containing 33 statements. And the alternative answer is very often given score of 4 (four), often given score of 3 (three), sometimes given score of 2 (two), and never given score of 1 (one). From the results of this study, it is known that Achievement Motivation on Feild of Buisness of Fashion Department of the students from class XI at SMKN 3 Pekanbaru is strong enough category. This is evident from the recapitulation of the data, which is : 1. Like a challenging job, as many as 58,79% of respondents answered very often and often. 2. Want more feedback on successes and failures, in this indicator as many as 59,6 % of respondents answered very often and often. 3. Positif interpersonal relationship, as many as 59,5 % of respondents answered very often and often. 4. Desire leads to achievement, in this indicator, as many as 53,1% of respondents answered very often and often. It means that Achievement Motivation on Feild of Buisness of Fashion Department of the students from class XI at SMKN 3 Pekanbaru classified in strong enough category.Key words : Achievement Motivation, Feild of Buisness, Fashion Department